QUANTIFICATION OF SYNAPTIC DENSITY IN CORTICOSTRIATAL PROJECTIONS FROM RAT MEDIAL AGRANULAR CORTEX - Reep, Roger L. (2008)
Medial agranular cortex (AGm) has a prominent bilateral projection to the dorsocentral striatum (DCS). We wished to develop a normal baseline by which to assess neuronal plasticity in this corticostriatal system in rats with neglect resulting from a unilateral lesion in AGm, followed by treatment with agents that promote sprouting and functional recovery in other systems. Injections of biotinylated dextran amine were made into AGm in normal rats, and unbiased sampling was used to quantify the density of axons and axonal varicosities present in DCS (the latter represent presynaptic profiles). Labeling density in contralateral DCS is approximately half that seen in ipsilateral DCS (this ratio is 0.50 for axons, 0.55 for varicosities). The ratio of varicosities is stable over a greater than seven-fold range of absolute densities. There is no consistent relationship between the absolute density of axons and axon varicosities; however, the ratio measures are strongly correlated. We conclude that changes in the contralateral/ipsilateral ratio of axon density after experimental treatments do reflect changes in synaptic density, but axon varicosities are likely to be the most sensitive anatomical parameter by which to assess plasticity at the light microscopic level.